Is there a predictive association between vitamin D concentrations and lower respiratory tract infections in infants? (Annals of Medical Research, 2019)
Aim: Vitamin D deficiency have been estimated to be endemic in the worldwide and in each age group and also it is reported that vitamin D has important effects on both natural and acquired immunity and there may be a relationship between deficiency and predisposition to infections The aim of this study is to investigate whether serum vitamin D level are effective in infant lower respiratory tract infection which is one of the most mortal infectious diseases in worldwide. Material and Methods: In our study, between October 2016 and January 2018 in Department of Pediatrics, the data of 418 infants with LRTI and their ages ranging from 5 to 24 months and were examined retrospectively. Vitamin D levels were studied in 106 of this patients. Results: In group-1, the mean duration of vitamin D supplementation was 4.9 months, while the mean in group-2 was 8.6 months. Breastfeeding time was 3.27 months in group 1 while it was 5.71 months in group 2. Both the duration of breastfeeding and the duration of vitamin D supplementation were shorter in group 1 than in group 2.Those difference between the groups was in terms ofstatistically significant (p< 0.05) Conclusion: Vitamin D deficiency in infants may be associated with LRTI, and even vitamin D deficiency may be a predisposing factor for severe LRTIs and also the frequency and severity of LRTIs can be reduced with optimal serum levels of vitamin D.
Keywords: Infant; LRTI; Vitamin D